Communication Strategy Based on Interactive Games in Climate Change Education by Predikt Tangguh Indonesia - Annisaa Larasati Oetomo; Wahyu Budi Priatna (Communica : Journal of Communication, 2026)
This study analyzes PT Predikt Tangguh Indonesia’s communication strategy for climate change education, focusing on the innovative integration of the GenerAksi board game and Instagram-based edutainment media. By employing interactive and participatory two-way communication, these approaches enhance audiences’ understanding, engagement, and motivation toward climate action. GenerAksi promotes collaborative experiential learning, enabling participants to explore climate risks and solutions in relatable real-life scenarios. Meanwhile, Instagram expands outreach and stimulates continuous involvement in climate discussions. Unlike dominant climate education approaches that remain one-way and school-centered, this study highlights the novelty of combining offline and digital interactive platforms as a unified community-oriented communication method. The findings provide insight into how innovative communication strategies can strengthen public awareness and meaningful participation in climate change education in Indonesia.